Viable pregnancy in a horn of a bicornuate uterus mimicking abruptio placenta: a case report (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2016)
Congenital abnormalities of the uterus have a prevalence of 1-10% in the general population. This case report is of  a bicornuate uterus mimicking abruptio in pregnancy. A caesarean section was done and a live female baby was  delivered. The case highlights the importance of a careful first trimester ultrasound for early detection of such cases